Regulation of cannabinoid receptor gene expression and endocannabinoid levels in lymphocyte subsets by interferon‐β: a longitudinal study in multiple sclerosis patients. (January 2015) - Sánchez López, A. J.; Román‐Vega, L.; Ramil Tojeiro, E.; Giuffrida, A.; García‐Merino, A.
Summary Evidence suggests the involvement of the cannabinoid system in the pathogenesis of multiple sclerosis (MS). We studied cannabinoid receptor (CB)1 and CB2 receptor gene expression in B, natural killer (NK) and T cells from MS patients before and after 1 year of interferon beta therapy, and compared these levels to those of healthy controls. We also measured the production of the endocannabinoids anandamide (AEA) and 2‐arachidonoylglycerol (2‐AG) and the gene expression of the endocannabinoid‐degrading enzyme fatty acid amide hydrolase (FAAH) in these cells. Prior to interferon therapy, MS patients showed significantly elevated CB2 expression in B cells, but not in T or NK cells. These levels decreased gradually within 6 months to 1 year of interferon treatment. CB1 expression was elevated in all cell subsets, but only reached statistical significance in T cells; all levels decreased progressively over time. Before treatment, AEA but not 2‐AG levels were significantly elevated in the three cell populations; after 1 year of treatment, all values decreased to control levels. The expression of FAAH was unchanged. The different expression of cannabinoid receptor genes and the increased level of AEA in lymphocytes point to a possible role of the cannabinoid system in MS immune response and its modulation by interferon.